How to resume elective orthopaedic surgical procedures during the COVID-19 pandemic?
This document was prepared by the College of Orthopedics of the Portuguese Medical Association with the aim of developing the guidelines on the resumption of elective surgical activity in Orthopedics during the COVID-19 pandemic. It sets the criteria that allow the prioritization of surgeries according to the severity of the clinical situation, based on existing and published classifications. Moreover, it provides an organizational model for patient preparation and describes the patient pathways in the preoperative, intraoperative and postoperative periods. It also describes safety rules for elective surgery and a model for monitoring patients after discharge according to scientific evidence.